PENGARUH KUALITAS PRODUK TERHADAP MINAT BELI ULANG PRODUK ELEKTRONIK PADA TOKO SINAR MUTIARA GORONTALO - Zainal Abidin Umar (Jurnal Ilmiah Ekonomi Manajemen: Jurnal Ilmiah Multi Science, 2016)
The purpose of this study was to determine the effect on product quality buying interest on electronic products in store Sinar Mutiara Gorontalo. This research was conducted 4 months is February to May 2014. The sampling method is non probabilty the technique performed by accidental sampling.Test results show the validity of the instrument rhitung rtabel means a valid and reliability is above 0.6 means reliable. The research results showed that multiple regression analysis, Y = α + βX + ɛ = 1.831 + 0,519X. The results of t test showed positive influence product quality variables significant to buy consumer interests. The results showed that the F test of F F table with a significance of 0.000 means that ditawakan Fit models or models that can be used to predict problems in this study. The correlation coefficient product quality has a strong correlation with the dependent variable. The coefficient of determination (R2) shows the contribution of 0.387 or 38.7% of the quality of the product to the consumer buying interest, while the remaining 0.613 or 61.3% in the form of the contribution of other factors not examined as brand image, quality of service, location effort, mix price, promotion and others. Keywords: quality products and interests buy